The Administrative Impact of the Qudama Family in Damascus in the Sixth and Seventh Centuries AH (The International Journal of Educational Sciences and Arts, 2024)
The study dealt with the position of the Al Qudama family on assuming administrative positions, and it also talked about the positions held by some members of the family, especially the judiciary, and that some of them held the highest judicial position, which is the chief judge. The details of this position were discussed, including its definition, origin, and who held it from the family. He mentioned the leadership of some family members in mosques and their preachers, and the research mentioned the teaching of family members, and all of this in the sixth and seventh centuries AH, in Damascus in general and Salihiyya in particular, and the influence of this family on these positions, in the Ayyubid and Mamluk states.
Keywords: Al Qudama Family; Administrative Positions; Administrative Impact; Damascus